CTLA-4 +49A/G Polymorphism Increases the Susceptibility to Bladder Cancer in Chinese Han Participants: A Case-Control Study. (1st December 2020) - Mao, Fei; Niu, Xiao-Bing; Gu, Shuo; Ji, Lu; Wei, Bing-Jian; Wang, Heng-Bing
Abstract : Cytotoxic T cell antigen-4 (CTLA-4) is reportedly involved in the development of bladder cancer (BC). This research was designed to address the potential link between the +49A/G polymorphism in CTLA-4 gene and BC susceptibility. In total, 355 BC cases and 435 match controls from Chinese Han individuals were included eventually. The PCR-RFLR method was utilized to screen for this polymorphism. The +49A/G polymorphism was shown to increase the risk of BC. Subgroup analyses showed that this polymorphism was linked to an increased susceptibility to BC among individuals aged < 60 years, smokers and drinkers. Additionally, this polymorphism significantly correlated with tumor node metastasis and tumor size (≥3 cm). To sum up, this study reveals that the CTLA-4 +49A/G polymorphism could increase the risk of BC in Chinese Han people. Further large cohort studies with enough sample sizes are urgently warranted to verify the findings of this present study.